ETIOPATHOGENESIS OF ISCHEMIC HEART DISEASES AND MECHANISM OF PATHOGENETIC INFLUENCE ON OTHER ORGAN SYSTEMS. - Toshpulatov Sardorjon Sarvar Ogli; Abduraupov Diyorbek Zafar Ogli; Adilbekova Dilorom Bakhtiyarovna (Western European Studies, 2024)
Ischemic heart disease or ischemic heart disease (IHD) is a chronic or acute disorder of blood supply to the myocardium (the muscular layer of the heart). This condition is caused by insufficient supply of oxygen to the heart. It occurs when the arterial blood supply to the heart muscle is limited due to damage to the coronary vessels. Acute form of ischemic heart disease - myocardial infarction, chronic form - angina pectoris. Cardiovascular diseases occupy the leading place in the sad list of causes of death in many developed countries. In recent years, there is a trend of decreasing death from this cause. Since 2015, the death rate from cardiovascular diseases has accounted for less than half of all deaths and continues to decline. This article is about the treatment of patients with ischemic heart disease, the article talks about the types of congenital heart defects, their causes and complications observed in patients with the disease, treatment methods and measures aimed at their prevention
Keywords: ischemic heart disease; angina pectoris; mitral valve insufficiency